Book Review: MUSLIM SANZIJING: SHIFTS AND CONTINUITIES IN THE DEFINITION OF ISLAM IN CHINA by Roberta Tontini - Min Ke-qin, Omar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2023)
Roberta Tontini, Muslim Sanzijing: Shifts and Continuities in the Definition of Islam in China. Boston, Brill, 2016. 246 pp. ISBN 978-90-04-31925-7 (E-book). Like the well-received works of Zvi Ben-Dor Benite, James Frankel, and Kristian Petersen, Roberta Tontini’s Muslim Sanzijing: Shifts and Continuities in the Definition of Islam in China is a prominent scholarly work on textual analysis in the Chinese Islamic literature of the Han Kitab genre. In her book, the young scholar Tontini focuses her study on selected Islamic primers written in a three-character format (three-character classics of Islam) to "initiate Chinese Muslims in the basic tenets of Islam" (p. 8). She mainly discusses the Sanzijing genre of Chinese Islamic literature, one of the writing styles of Han Kitab literature. The Sanzijing, as one knows, is one of the Chinese classics, a very popular small book composed by an unknown author, in the form of three Chinese characters ("sanzi” 三字 denotes three characters while “jing” 经 signifies "classic") with the rhyme scheme. This form is easy for children to read by heart, at the same time installing in them the basic knowledge of Confucian teachings, Chinese history, geography, astronomy, and more. Chinese Muslim intellectuals knew well the role played by this literature in child education, thereby boldly adopting this form of Chinese literature into Muslim education. The first Chinese ‘alim who employed this form in Muslim education in China was Liu Zhi 刘智 (d. 1764), a prolific Chinese Muslim writer whose works, especially of Tianfang Dianli (Elegant Rituals of Islam) and Tianfang Sanzijing (Three-Characters Classic of Islam) are the main subjects of discussion in Tontini’s current work.